Analysis of Learning Outcome in Arabic Subject Among the Student of Muhammadiyah Boarding School Alabio, South Kalimantan - Zikra, Afdhala Khaira; Madjid, Muh. Naim; Güler, İsmail (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2025)
Abstract This study aims to analysis the students’ Arabic language learning outcomes in Muhammadiyah Boarding School Alabio, South Kalimantan, Indonesia, at junior high school level. This research used a quantitative method and statistical analysis approach including normality tests, homogeneity tests, and independent sample t-tests. There are sixty respondents by using a simple random sampling technique and they were divided into two student groups, boarding school and non-boarding school. Data were collected through observation, interviews, and documentation. Most important findings indicated a significant difference in Arabic learning outcomes for both groups, where the boarding school students obtained high average scores with the t-test result 0.008 (p < 0.05), confirming that the students’ residential environment has a statistically significant impact on their academic performance in Arabic language. The main factors supported the students’ learning outcomes is creating the effective learning environment by accessibility of additional instruction and Arabic practice in daily communication.